(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The role of psychology has increased over the last few years. People have gone under extreme metal pressure during COVID 19 pandemic. Lock down, quarantine, and deaths of people have traumatised everyone. Suddenly the number of academic researchers has turned to this issue. Several studies have been conducted to understand the psychological issues among people. Present study has focused upon the private teachers in Delhi NCR. Researchers have clubbed 38 questions related with teachers’ psychological aspects of private school teachers. The questionnaire has been tested for reliability (Cronbach’s Alpha 0.751). Further Factor analysis has extracted 04 components viz. Job Satisfaction, Motivation, Organizational Commitment, and Employee Performance. Researchers have found that there is significant difference in the opinion of teachers about extracted psychological variables. The teachers are having their opinion on a positive side even after the pandemic. Researchers have found that teachers have adopted the changes in the environment and feel satisfied with new normal.